Knock-Out of CmNAC-NOR Affects Melon Climacteric Fruit Ripening - Liu, Bin; Santo Domingo, Miguel; Mayobre, Carlos; Martín-Hernández, Ana Montserrat; Pujol, Marta; Garcia-Mas, Jordi (Frontiers in Plant Science, 2022)
Fruit ripening is an important process that affects fruit quality. A QTL in melon, ETHQV6.3, involved in climacteric ripening regulation, has been found to be encoded by CmNAC-NOR, a homologue of the tomato NOR gene. To further investigate CmNAC-NOR function, we obtained two CRISPR/Cas9-mediated mutants (nor-3 and nor-1) in the climacteric Védrantais background. nor-3, containing a 3-bp deletion altering the NAC domain A, resulted in ~8 days delay in ripening without affecting fruit quality. In contrast, the 1-bp deletion in nor-1 resulted in a fully disrupted NAC domain, which completely blocked climacteric ripening. The nor-1 fruits did not produce ethylene, no abscission layer was formed and there was no external color change. Additionally, volatile components were dramatically altered, seeds were not well developed and flesh firmness was also altered. There was a delay in fruit ripening with the nor-1 allele in heterozygosis of ~20 days. Our results provide new information regarding the function of CmNAC-NOR in melon fruit ripening, suggesting that it is a potential target for modulating shelf life in commercial climacteric melon varieties.